Aspek Religiusitas Dalam Keputusan Pembelian Produk Halal (Studi tentang labelisasi halal pada produk makanan dan minuman kemasan) - Dwiwiyati Astogini; Wahyudin Wahyudin; Siti Zulaikha Wulandari (Ilmu Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Unsoed, 2011)
ABSTRACTReligiosity is one's religion appreciation concerning the symbols, beliefs, values and behaviors that are driven by spiritual forces. Indonesian consumer behavior in products purchasing decisions, also can be considered as a part of activities related to the religiosity. This study aims to determine the influence of Religiosity on halal product purchasing decisions, and examine the most influential religiosity dimension on purchase decisions of packaging food and beverages, as well as consumer perception of MUI’s halal logo and company’s halal logo. Target population in this study is consumers in Purwokerto, which is buying packaging food and beverages and aged over 15 years and make a purchase decision based on his own. Samples of the 100 respondents obtained by accidental sampling method. This study used five Religiosity dimension proposed by Stark and Glock as independent variables : Ritual, Ideological, Intellectual, experience and Consequences Dimensions. The dependent variable is consumer purchasing decisions of packaging of food and beverages. By using multiple regression analysis showed that Religiosity has no effect on consumer purchasing decisions of packaging food and beverages and Consequences Dimension is the most influential religiosity dimension. Also note that most consumers believe both LPPOM-MUI halal logo and halal logo issued by the company. Keywords: Religiosity, Consumers decision, Halal Food and Beverages